RUSSIAN NIHILISM AND ITS SIDE IN DOSTOEVSKY - Peña, Juan Manuel (Disertaciones, 2019)
This article explores the assumptions of Russian nihilism and the way in the work The Brothers Karamazov and in general in the works of Dostoevsky criticisms of this Russian movement. We will see that his literary works will go beyond the limits of the issues raised by this particular form of nihilism that had mainly political pretensions.
Keywords: Dostoevsky; literature; nihilism